PBRM1 mutation as a predictive biomarker for immunotherapy in multiple cancers - Dai, Jiali; Cui, Yanan; Liang, Xiao; Xu, Jiali; Li, Jun; Chen, Yu; Zhang, Erbao; Guo, Renhua (Frontiers in Genetics, 2023)
Background: There has been evidence that Polybromo-1 (PBRM1) mutation was closely associated with immunotherapy response in clear cell renal cell carcinoma (ccRCC). However, it remains incompletely unclear whether PBRM1 mutations correlate with ICI response in pan-cancer. Methods: The clinical data and whole exome sequencing (WES) data were collected from seven published immunotherapy studies to evaluate the association between PBRM1 mutation and ICIs efficacy in the discovery cohort. In order to provide further insight into the relationship between PBRM1 and immunity, we analyzed a relatively large sample as a validation cohort. Moreover, we also collected the clinical data and mutation information of 134 non-small cell lung cancer (NSCLC) patients from the First Affiliated Hospital of Nanjing Medical University to verify the findings. Gene set enrichment analysis (GSEA) was used to evaluate the relationship between PBRM1 and immune-related pathway. Results: Our results found that PBRM1 mutation were associated with immune response in the discovery cohort (progression-free survival [PFS]: hazard ratio (HR) = 0.51, 95% CI: 0.28–0.95, P = 0.030; objective response rate [ORR]: 47.92% vs 28.21%, P = 0.0044; disease control rate [DCR]: 72.92% vs 47.53%, P = 0.0008). In the validation cohort, the patients with PBRM1 mutation had a longer overall survival (OS) (HR =0.69, 95% CI: 0.53–0.91, P = 0.006). In our NSCLC cohort, PFS, ORR and DCR had obvious superiority in the patients with PBRM1 mutation than those without PBRM1 mutation (PFS: HR =0.268, 95% CI: 084–0.854, P =0.04, ORR: 55.56% vs 20.00%, P = 0.027, DCR: 100% vs 75.20%). Using the gene-set enrichment analysis (GSEA) in TCGA cohorts, PBRM1 mutation was closely related to immune efficacy and immune microenvironment, including killer cell mediated immunity regulation, cell cytokine production, CD8+ T cell activation and MHC protein binding process. Conclusion: There is a strong correlation between PBRM1 mutation and prognosis and immune response. Based on the findings, PBRM1 mutation may be a promising immunotherapeutic signature that could guide clinical management and personalized immunotherapy.